Financial Flexibility and Role in Raising the Level of Financial Performance: An Analytical Study of a Sample of Bbanks listed in the Iraqi Stock Exchange for the Period (2016-2020) - نوري كاكه حمه العطار خانم; عزت جلال آلاء (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The current research dealt with one of the important topics in the field of financial and banking sciences, which is financial flexibility and its role in raising the level of financial performance of banks, as financial flexibility helps banks to adapt to various sudden circumstances and situations that the financial institution may be exposed to, with the possibility of exploiting those shocks for the benefit of the institution, and the study aimed to measure the correlation and impact of financial flexibility variables on financial performance and its indicators. Due to poor planning and management, obsolescence of banking services, turmoil in the environment, and stagnation of banking procedures, which resulted in a decline in the financial performance of banks, two main hypotheses were developed for test them, and the research population included the banks listed on the Iraq Stock Exchange (44) banks, while the sample included (30) banks for the period (2016-2020). The data were analyzed by a set of statistical tests using (SPSS V.26) and (Excel 2019) statistical software. The most important finding is that financial flexibility and its variables have a significant correlation and impact on financial performance and its indicators, and those profitability indicators are unstable, specifically the rate of return on assets and the rate of return on equity (up and down) for most banks in the research. We also conclude that the failure of banks to achieve profits compared to the total assets they own as well as the total equity is a result of inflexibility and mismanagement of those assets, which led to the failure to achieve good performance. The research also recommended a set of recommendations, perhaps the most important of which is the need for banking institutions (the research sample) to be interested in applying financial flexibility to raise financial performance indicators, especially profitability indicators, specifically the rate of return. On assets, and rate of return on equity as they are the most explanatory measurement of performance and how well banks are making profits.